2007
DOI: 10.1007/s11947-007-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Trace Metals Concentration on Citric Acid Production by Aspergillus niger NRRL 2001

Abstract: Citric acid is nowadays produced by submerged fermentation of Aspergillus niger. The process yield depends on the composition of the medium, as well as on the microorganism strain. In this work, the effect of Fe +3 , Zn +2 , and Mn +2 on citric acid production by A. niger NRRL 2001 is presented. The culture medium composition was glucose (120 g/L) KH 2 PO 4 (1.0 g/L); K 2 HPO 4 (1.0 g/L), MgSO 4 .7H 2 O (0.5 g/L), (NH 4 ) 2 SO 4 (3.0 g/L). The ions Fe +3 , Zn +2 , and Mn +2 had their concentrations changed acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Since detailed analysis on trace metal concentration in A. niger media showed that citric acid production could be increased by combining low levels of Mn 2+ with high levels of Fe 2+ [ 11 ], and because Fe 2+ is a cofactor of hemoglobin to bind oxygen, we investigated this combination using medium 13. This medium contained a high concentration of Fe 2+ and no Mn 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Since detailed analysis on trace metal concentration in A. niger media showed that citric acid production could be increased by combining low levels of Mn 2+ with high levels of Fe 2+ [ 11 ], and because Fe 2+ is a cofactor of hemoglobin to bind oxygen, we investigated this combination using medium 13. This medium contained a high concentration of Fe 2+ and no Mn 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…The fungus was grown in PDA medium at 30 • C for 5 days and then kept in the refrigerator (4 • C) for up to 3 months. To obtain a concentrated spore suspension, the spores were transferred from the plates to a medium of corncobs and peptone [36]. After 5 days at 30 • C, the medium was flooded with a sterile Tween 80 solution (0.5% v/v), mixed with a glass rod, and the suspension was collected.…”
Section: Microorganismmentioning
confidence: 99%
“…A cartridge was conditioned and, the sample (1 mL) adjusted to pH 9, loaded through the cartridge ensuring a flow rate of 0.3 mL/min. The interferences were washed out using 1 mL of deionized water, while acid compounds were eluted five times with 0.5 mL of HCl (1 N), diluted with the mobile phase to a final volume of 5 mL, filtered through 0.2 µm syringe filter and later injected on HPLC [21,22].…”
Section: Sample Preparationmentioning
confidence: 99%